Gain Enhanced Quad-Band AMC Backed Printed Antenna with Fractal Geometry - Krishnan A.M.J.; Samantaray D.; Mohamed A.; Saha C.; Bhattacharyya S. (My University, 2025)
In this paper, a gain enhanced quad band fractal based printed antenna backed with artificial magnetic conductor (AMC) has been proposed for S and C-band applications. The proposed antenna is designed to operate at 2.7 GHz, 4.84 GHz, 5.58 GHz and 5.9 GHz with highly realized gains of 8 dBi, 10.1 dBi, 6.9 dBi and 8.5 dBi respectively. The realized antenna provides narrow band impedance bandwidths of 40 MHz, 50 MHz, 55 MHz and 120 MHz in the four operating frequency bands. The ground, AMC unit cell, reflector sheet and the radiating patch of the antenna have been made using copper while Styrofoam has been used as the substrate material. Therefore, the proposed design is a promising candidate for low cost, high gain and multi-band structure mount antenna applications. © 2020 Indian Radio Science Society.